MAC-Sparing Effect of Transdermal Fentanyl in Sevoflurane-Anesthetized Sheep - Lauren Duffee (Sciendo, 2018)
Transdermal fentanyl allows for consistent plasma concentrations of a potent synthetic μ-opioid receptor agonist and can provide constant post-operative analgesia for up to 72 h. The aim of this study was to determine the reduction of the minimum alveolar concentration of sevoflurane (MACSEVO) by transdermal fentanyl in nonpregnant ewes. Nine sheep were mask induced with sevoflurane (SEVO in oxygen). MACSEVO determinations involved electrical current applied to the lateral metacarpus as a supramaximal stimulus and measurements in duplicate. Seven days later, a fentanyl patch (75 μg/h) was applied to each sheep and 15.1 ± 1.8 h later the MAC re-determined (MACSF). MACSF was 1.99 ± 0.32 %, corresponding to 25.6 ± 8.1 % reduction from MACSEVO (P < 0.001). Transdermal fentanyl produces a significant MACSEVO-sparing effect with minimal effect on cardiovascular parameters.